Isolated short femur alone in the mid-trimester fetus is not associated with increased risk of aneuploidy: a clinical study in eastern India - Chaudhury, Kalyansree; Mukherjee, Kanchan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Identifying the soft markers during the anomaly scan improves the detection rate of fetal aneuploidy at the cost of increased false-positive rate and consequent increased interventions. Isolated short femur is one such soft marker that puts the clinician into a dilemma. The aim of this study is to assess the risk of aneuploidy in the fetus with isolated short femur, so that the data can be used for counseling the prospective parents in our population. Methods: In this retrospective study, all the fetuses of 43 mothers, at the time of ultrasound scan between 18-20 weeks of gestation for fetal anomaly, were found to have isolated short femur. Depending on the presence of other soft markers, the mothers were divided into two groups, group I containing mothers having fetus with only isolated short femur and group II containing mothers having fetus with one or more soft marker in addition to isolated short femur. The chromosomal status of all the fetuses was checked by either amniocentesis and karyotyping or birth of a phenotypically normal baby. Results: There was no aneuploidy in the group I containing fetuses with isolated short femur only. Our results are consistent with other international studies. Conclusions: Isolated short femur alone does not increase the existing risk of fetal aneuploidy.